Studi Pengaruh Kontaminasi Properti Rheology Water Based Mud di Lapangan Sunyu - Abdullah Rizky Agusman (JURNAL BHARA PETRO ENERGI, 2022)
This project focuses on Investigation of effect of contaminants on the Rheological Properties of Water-based Drilling Mud. For any drilling operation to be termed successful, care must be taken during the selection and application of the drilling fluid which are key factors that should be considered. Any actions contrary to carefully selection and application of drilling fluids could have very dire consequences. Based on the experiment work done on water base mud system to ascertain the effect of contaminants (salt, silica sand, cement and carbonate) on the rheological properties and performance of the mud, it shows that the presence of a contaminant on the drilling mud either reduces or increases the rheological properties of the mud system and in turn affects the rate of penetration, it performance and also poses serious drilling problems. It was observed that the presence of Sodium salt in the mud system increased the fluid loss into the formation. It was further observed that while Apparent Viscosity, Gel Strength increases as the mass increase from 1g to 5g, the pH and Plastic Viscosity almost did not change. The Yield point increases little.  With Cement as contaminant, it shows all rheological properties of the mud increased markedly, as the quantity of the cement used is increased from 1g to 5g and the pH does not change. Silica contamination has not showed any marked effect on the nature of the drilling mud. In fact, the more the amount of the contaminant (Silica) is added, the closer it properties are to the blank sample that do not have contaminants. The carbonate effect is largely on the Gel strength which decreases as the amount of added carbonate increases. The pH has no charges, which also means carbonate keeps the mud in it alkaline state, as it was the case with cement. Reference: Ali K., Vipulanandan C., Richardson D. (2013): Salt (NaCl) contamination of the resistivity and plastic viscosity of bentonite drilling mud, Proceedings of the center for innovative grouting materials and technology (CIGMAT) Conference & Exhibition. Bradford, B. B.: "Setting Cement Plugs Requires Careful Planning", Oil & Gas Journal, pp. 102, 1982. Cavanagh, P.H., Johnson, C. R., LeRoy-Delage, S., DeBruijn, G. G., Cooper, I., Guillot, D. J., Bulte, H., and Dargaud, B. (2007): "Self-Healing Cement - Novel Technology to Achieve Leak-Free Wells", SPE-105781 presented at the SPE/IADC Drilling Conference, Amsterdam, The Netherlands, 20-22 February. Chaney P.E, 1942. A Review of recent advances in drilling mud control, Drilling and Production Practice, American Petroleum Institute, 31-46.  Charlez P. H and Heugas O. (1991): Evaluation of Optimal Mud Weight In Soft Shale Levels, American rock mechanics association, The 32nd U.S. Symposium on Rock Mechanics (USRMS), 10-12 July, Norman, Oklahoma Chen, C.P. Tan and C. Detournay, (2002), the impact of mud filtration on wellbore stability fracture rock masses, SPE/ISRM 78241 presented at the SPE/ISRM rock mechanics conference held in Irving, Texas Dosunmu .A. and Ogunrinde .J. (2010) “Development of Environmentally Friendly Oil Based Mud using Palm Oil and Groundnut Oil”. SPE 140720. Paper presented at the 34th Annual International Conference and Exhibition in Tinapa-Calabar, Nigeria, July 31st- August 7th, 2010. Dusseault, M.B., Gray, M.  N., and Nawrocki, P.A.:  "Why Oil wells Leak:  Cement Behavior and Long-Term Consequences", SPE  64733 presented at the SPE International Oil and Gas Conference and Exhibition, Beijing, China, 2000. El-Sayed, A. A. H.: "Effect of Drilling Muds Contamination on Cement Slurry Properties", Fourth Saudi Engineering Conference, pp. 287-295, 1995. Ezzat, A.M., Rosser, H.R. & Al-Humam, A.A., 1997. ‘Control of Microbiological Activity in Biopolymer-Based Drilling Muds’, SPE paper 39285. Fadairo Adesina, Adeyemi Abiodun, Ameloko Anthony, Falode Olugbenga, (2012) “Modelling the Effect of Temperature on Environmentally Safe Oil Based Drilling New Technologies in the Oil and Gas Industry Mud Using Artificial Neural Network Algorithm” Journal of Petroleum and Coal 2012, Volume 54, Issue 1. Fadairo Adesina, Ameloko Anthony, Adeyemi Gbadegesin, Ogidigbo Esseoghene, Airende Oyakhire (2012) “Environmental Impact Evaluation of a Safe Drilling Mud” SPE Middle East Health, Safety, Security, and Environment Conference and Exhibition held in Abu Dhabi, UAE, 2–4 April 2012, SPE-152865-PP Fosso, S.W., Tina, M., Frigaard, I. A., and Crawshaw, J.  P. (2000):  "Viscous-Pill Design Methodology Leads to Increased Cement Plug Success Rates; Application and Case Studies from Southern Algeria", SPE  62752 presented at the IADC/SPE Asia Pacific Drilling Technology, Kuala Lumpur, Malaysia. Gursat Altun and Umran Serpen (2005) “Investigating Improved Rheological and Fluid Loss Performance of Sepiolite Muds under Elevated Temperatures” Proceedings World Geothermal Congress, Antalya, Turkey, 24-29 April 2005 Hssiba, K J. and Amani, M. 2013. The Effect of Salinity on the Rheological Properties of Water Based Mud under High Pressures and High Temperatures for Drilling Offshore and Deep Wells Earth Science Research; Vol. 2, 1. Hussain H. Al-Kayiem et al. (2010): Simulation of the Cuttings Cleaning During the Drilling Operation. American Journal of Applied Science 7(6), p 800-806. Mahmood Amani and Khaled J. H (2012): Salinity Effect on the Rheological Properties of Water Based Mud under High Pressures and High Temperatures of Deep Wells, SPE-163315-MS presented at SPE Kuwait International Petroleum Conference and Exhibition, 10-12 December, Kuwait City, Kuwait Nasution, M. M., Rasyid, A., & Pahrudin, G. (2022). Desain Formulasi Lumpur Untuk Pemboran Panas Bumi Di Sumur GG-01. JURNAL BHARA PETRO ENERGI, 1(1), 11-18. Nelson, E.B. and Guillot, D. (2006): "Well Cementing" 2ndEdition, Schlumberger, Sugar Land, Texas. Remillard S. C, “Applications of Nanotechnology within the Oil and Gas Industry,” Oil and Gas Review, Vol. 8, 2010, pp. 1-108.Oilfield Glossary Sachez G; N. León, M. Esclapés; I. Galindo; A. Martínez; J. Bruzual; I. Siegert, (1999) “Environmentally Safe Oil-Based Fluids for Drilling Activities” SPE 52739, Paper presented at SPE/EPA Exploration and Production Environmental Conference held in Austin, Texas. Tellisi, M., Ravi, K., and Pattillo, P.: "Characterizing Cement Sheath Properties for Zonal Isolation", WPC-18-0865 presented at the 18th World Petroleum Congress, Johannesburg, South Africa, September 25 - 29, 2005. Xiaoqing .H. and Lihui .Z., (2009) “Research on the Application of Environment Acceptable Natural Macromolecule Based Drilling Fluids” SPE 123232, Paper presented at the SPE Asia Pacific Health, Safety, Security and Environment Conference and Exhibition held in Jarkata, Indonesia, 4-6 August 2009.